Effect of Interactions Between Lower Airway Bacterial and Rhinoviral Infection in Exacerbations of COPD - Wilkinson, Tom M.A. (Chest, 2006)
STUDY OBJECTIVES: The inflammatory responses and associated clinical severity of COPD exacerbations are greatly variable, and the determinants of these factors are poorly understood. We examined the hypothesis that bacteria and viruses may modulate this heterogeneity and that interactions between bacterial and viral infection may affect changes in airway bacterial load and the clinical features and inflammatory responses of exacerbations in patients with COPD. DESIGN: Prospective cohort study. SETTING: Outpatient Department, London Chest Hospital, London, UK. PATIENTS: Thirty-nine patients with COPD. MEASUREMENTS: We prospectively studied 56 COPD exacerbations, obtaining clinical data and paired sputum and serum samples at baseline and exacerbation. Qualitative and quantitative microbiology, polymerase chain reaction detection for rhinovirus, and estimation of cytokine levels by enzyme-linked immunosorbent assay were performed. RESULTS: A total of 69.6% of exacerbations were associated with a bacterial pathogen, most commonly Haemophilus influenzae. Rhinovirus was identified in 19.6% of exacerbations. The rise in bacterial load at exacerbation correlated with the rise in sputum interleukin (IL)-8 (r = 0.37, p = 0.022) and fall in FEV(1) (r = 0.35, p = 0.048). Exacerbations with both rhinovirus and H influenzae had higher bacterial loads (10(8.56) cfu/mL vs 10(8.05)cfu/mL, p = 0.018) and serum IL-6 (13.75 pg/mL vs 6.29 pg/mL, p = 0.028) than exacerbations without both pathogens. In exacerbations with both cold symptoms (a marker of putative viral infection) and a bacterial pathogen, the FEV(1) fall was greater (20.3% vs 3.6%, p = 0.026) and symptom count was higher (p = 0.019) than those with a bacterial pathogen alone. CONCLUSIONS: The clinical severity and inflammatory responses in COPD exacerbations are modulated by the nature of the infecting organism: bacterial and viral pathogens interact to cause additional rises in inflammatory markers and greater exacerbation severity.